Asemptomatik Hastada Mesane Tümörünü Taklit Eden Polipoid Sistit Olgusu - Voyvoda, Nuray; Devecı, Serkan; Saglıcan, Yesim (Fırat University, 2012)
Biz check-up sırasında abdominal ultrasonografi ile ortaya çıkarılan ve sonrasında yapılan sistoskopi ile de teyid edilen polipoid kitlesi olan 31 yaşında erkek hastayı sunduk. Hastaya transüretral rezeksiyon yapıldı. Rezeke edilen spesmenin histopatolojik tanısı polipoid sistitdi. Klinik, makroskopik ve radyolojik olarak polipoid kitleler çakışabilir ve histolojik değerlendirme gerekebilir.

We report a 31-year-old male with a polypoid mass that was revealed by abdominal ultrasound during a health checkup and was confirmed by subsequent cystoscopy. The patient underwent transurethral resection. Histological examination of the resected specimen showed polypoid cystitis. Clinical, macroscopic, and radiologic findings for polypoid masses may overlap; thus, histologic evaluation is required.
A Case of Polypoid Cystitis Mimicking Bladder Tumor in Asymptomatic Patient